2021
DOI: 10.5194/soil-7-1-2021
|View full text |Cite
|
Sign up to set email alerts
|

Altitude and management affect soil fertility, leaf nutrient status and Xanthomonas wilt prevalence in enset gardens

Abstract: Abstract. Enset (Ensete ventricosum) is a productive, drought-tolerant and multipurpose food security crop grown in the densely populated Ethiopian highlands. It is a so-called orphan crop, and its production suffers from a lack of information on proper soil fertility management and its interaction with bacterial wilt disease caused by the pathogen Xanthomonas campestris pv. musacearum. The aim of this study was therefore to assess soil–plant nutrient variation within enset home gardens at three altitudes (ran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 79 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…Other surveys have reported various XW hotspots throughout the years, for example with increased incidences in the Gedeo zone (McKnight-CCRP, 2013), the Hadiya zone (Wolde et al, 2016) or the West Shewa zone (Hunduma et al, 2015), but it is evident that XW forms a major constraint across all regions. No indication is found of changing XW susceptibility related to environmental conditions (in this case with altitudinal variation), although this association has been suggested (Yemataw et al, 2020;Gebre et al, 2021;Shara et al, 2021).…”
Section: Discussionmentioning
confidence: 89%
“…Other surveys have reported various XW hotspots throughout the years, for example with increased incidences in the Gedeo zone (McKnight-CCRP, 2013), the Hadiya zone (Wolde et al, 2016) or the West Shewa zone (Hunduma et al, 2015), but it is evident that XW forms a major constraint across all regions. No indication is found of changing XW susceptibility related to environmental conditions (in this case with altitudinal variation), although this association has been suggested (Yemataw et al, 2020;Gebre et al, 2021;Shara et al, 2021).…”
Section: Discussionmentioning
confidence: 89%
“…Simpson's index is defined here as 1 -D, or the probability of selecting two individuals from different species, with replacement. The Shannon-Weaver diversity index accounts for both abundance and evenness of the landraces present and can be increased either by greater evenness or more unique landraces (Shannon and Weaver, 1949). The Shannon-Weaver index is defined as: H' = -Σ i p i ln p i Where: p i is the proportional abundance of species i.…”
Section: Methodology Study Areamentioning
confidence: 99%
“…Indeed, a perception bias in landrace environmental tolerances is observed. Namely the importance of drought tolerant landraces reportedly increased with altitude, whilst there is a tendency for more rain at higher elevations (Shara et al, 2021). At lower altitudes, farmers have more experience with drought, and as such have a better idea of which landraces are tolerant or susceptible to drought.…”
Section: Growing Conditions and Expected Yieldsmentioning
confidence: 99%
“…This could be attributed to fixation of P by SOM and aluminum (Al) in the soil. Shara et al [25] observed a decline in P with increasing altitude at sites in Ethiopia and attributed this decline to fixation by Al that increased with altitude. In the current study, mean P also generally declined with increasing altitude (c.f.…”
Section: The Yield Limiting Factors Computed Using the Boundary Line Analysismentioning
confidence: 99%